Comparación de los ensamblaje de artrópodos en distintos hábitats de la ecorregiones Campo & Malezales, Corrientes (Argentina) - Rodriguez, Carla Andrea (2015)
The ecoregion Field and malezales comprise about 30,000 km2 between the southeastern province of Misiones and northeast of Corrientes, Argentina. She is represented by a combination of patches of Paranaense Forest within a matrix of natural grasslands. We investigated and compared the arthropod assemblages in different habitat types (forest and grassland) of Field & Malezales ecoregion in the province of Corrientes. We carried out two samplings of arthropods on vegetation (spring 2006 and autumn 2007), in which eight sampling sites, widely separated by several kilometers. We take 10 samples randomly with a G-Vac (garden-vacuum) on vegetation. A total of 24,328 individuals, 1.225spp / morphospecies of arthropods in 22 orders, of which grassland (S=742spp N=15,406); while patches of forest (S=858spp N=8,922) the arthropods. The complementarity between arthropod an assemblage of forests and grasslands was high. The biggest contribution to the gamma diversity was given by β1, species turnover between samples from a site. Alpha diversity contributes greatly to regional diversity, with forest sites increased diversity. The greatest diversity of existing sites in the ecoregion environments are important and responsible registered diversity, so this should be taken into account in the planning of tasks aimed at the conservation of regional biodiversity.